Metabolomic profiling combined with network analysis of serum pharmacochemistry to reveal the therapeutic mechanism of Ardisiae Japonicae Herba against acute lung injury - Han, Xiao-Xiao; Tian, Yan-Ge; Liu, Wen-Jing; Zhao, Di; Liu, Xue-Fang; Hu, Yan-Ping; Feng, Su-Xiang; Li, Jian-Sheng (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is a common and devastating respiratory disease which associated with uncontrolled inflammatory response and transepithelial neutrophil migration. In recent years, a growing number of studies have found that Ardisiae Japonicae Herba (AJH) has a favorable anti-inflammatory effect. However, its serum material basis and molecular mechanism are still unrevealed in ALI treatment. In this study, metabolomics and network analysis of serum pharmacochemistry were used to explore the therapeutic effect and molecular mechanism of AJH against lipopolysaccharide (LPS)-induced ALI. 12 rats for serum pharmacochemistry analysis were randomly divided into LPS group and LPS+AJH-treated group (treated with AJH extract 20g/kg/d), which were administrated LPS (2 mg/kg) by intratracheal instillation and then continuously administered for seven days. Moreover, 36 rats for metabolomic research were divided into control, LPS, LPS+AJH-treated groups (5, 10 and 20 g/kg/d), and LPS+dexamethasone (Dex) (2.3 × 10 -4 g/kg/d). After 1 hour of the seventh administration, the LPS, LPS+AJH-treated and LPS+Dex groups were used LPS to induce ALI by intratracheal instillation. The serum pharmacochemistry profiling was performed by UPLC-Orbitrap Fusion MS to identify serum components, which further explore the molecular mechanism of AJH against ALI by network analysis. Meanwhile, metabolomics was used to select the potential biomarkers and related metabolic pathways, analyze the therapeutic mechanism of AJH against ALI. The results showed that 71 serum components and 18 related metabolites in ALI rat serum were identified.We found that 81 overlapping targets were frequently involved in AGE-RAGE, PI3K-AKT and JAK-STAT signaling pathways in network analysis. LPS+AJH-treated groups exerted protective effects against ALI by reducing the infiltration of inflammatory cells, and achieved anti-inflammatory efficacy by significantly regulating the interleukin (IL) 6 and IL10 levels. Metabolomics analysis shows that the therapeutic effect of AJH for ALI involves 43 potential biomarkers and 14 metabolic pathways, especially Phenylalanine, tyrosine and tryptophan biosynthesis and Linoleic acid metabolism pathways, to be influenced, which implied the potential mechanism of AJH in the ALI treatment. Our study initially elucidated its material basis and effective mechanism of AJH against ALI, which provided a solid basis for AJH application.